Genetic yield gain between 1942 and 2013 and associated changes in phenology, yield components and root traits of Australian barley - C. Mariano Cossani; Jairo Palta; Victor O. Sadras (Plant and Soil, 2022)
Background and Aims Barley breeding has increased yield over the last century, but the associated changes in the phenotype are largely unknown. Our aim was to quantify the rate of genetic gain in a collection of Australian barley cultivars representing seven decades of breeding, and the associated changes in the phenotype. Methods Thirteen barley cultivars were grown in the field at Roseworthy and Mintaro, South Australia, to evaluate shifts in phenology, yield, and its components. A subset of five cultivars was grown under controlled conditions to probe for changes in root traits and nutrient uptake. Results Grain yield increased at 16.0 ± 5.3 kg ha −1 yr −1 or 0.43 ± 0.15% yr −1 at Roseworthy, where average yield was 3.1 t ha −1 . There was no relation between yield and year of registration at Mintaro, where severe, extended frost disrupted reproduction. Changes in phenology with year of registration were not apparent. The main drivers of yield gain were grain number per m 2 and harvest index, with a minor contribution of shoot biomass. Root length density, specific root length, root extension rate, and nutrient uptake per cm of root length increased with year of registration. Conclusions The rate of genetic gain of Australian barley aligned with rates reported for other breeding programs worldwide and compared to 21.0 ± 2.3 kg ha −1 yr −1 for actual yield in Australian farms between 1961 and 2019. Changes in the growth and functionality of the root system highlight the indirect effects of selective pressure for yield and agronomic adaptation.